PENGEMBANGAN APLIKASI PENGGAJIAN BERBASIS WEB DENGAN METODE SDLC UNTUK MENDUKUNG EFISIENSI BISNIS PERUSAHAAN - Chandrika, Chandrika; Waliya Rahmawanti; Yuli Fitriyani; Julia Fajaryanti (Asosiasi Dosen Muda Indonesia, 2024)
In the modern era, the development of software has advanced rapidly. Various features and conveniences provided enable easier access to and use of information on the internet. One of the essential mediums in this context is websites. Websites have become a primary need for delivering necessary information and building trust and comfort in various business activities.This scientific writing adopts the System Development Life Cycle (SDLC) method, which includes the stages of analysis, design, implementation, and testing. In this study, a payroll application was successfully developed to support online attendance and payroll processes. The application testing was conducted using several web browsers, such as Google Chrome, Mozilla Firefox, and Microsoft Edge. The developed website can be accessed through http://localhost/payrol/.The test results showed that Google Chrome is the best browser due to its faster loading time compared to the others. With the operation of this website, the attendance and payroll processes in the company have become easier and more efficient for both administrators and employees. This application is expected to make a significant contribution to improving the company's operational efficiency.